2006
DOI: 10.3354/dao070037
|View full text |Cite
|
Sign up to set email alerts
|

Transmission of white sturgeon iridovirus in Kootenai River white sturgeon Acipenser transmontanus

Abstract: It is thought that white sturgeon iridovirus (WSIV) is transmitted vertically from adult white sturgeon Acipenser transmontanus to progeny, and that wild adults are carriers of this virus. Based on this assumption, egg disinfection trials were initiated using wild Kootenai River white sturgeon. Over 2 consecutive years, post-fertilized eggs were disinfected with iodine at concentrations ranging from 0 to 400 ppm. Eggs were incubated and progeny were reared on either de-chlorinated municipal or Kootenai River w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
14
0

Year Published

2007
2007
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(17 citation statements)
references
References 5 publications
3
14
0
Order By: Relevance
“…Initial attempts to isolate the virus in pure culture on white sturgeon cell lines were unsuccessful. This is similar to MRSIV (Kurobe et al 2011) and some isolates of WSIV (Hedrick et al 1990, Drennan et al 2006. We were able to detect Namao virus, although weakly, by cPCR when suspect tissues were inoculated and then incubated for prolonged periods on primary lake sturgeon cell lines but without evidence of CPE.…”
Section: Discussionsupporting
confidence: 73%
See 2 more Smart Citations
“…Initial attempts to isolate the virus in pure culture on white sturgeon cell lines were unsuccessful. This is similar to MRSIV (Kurobe et al 2011) and some isolates of WSIV (Hedrick et al 1990, Drennan et al 2006. We were able to detect Namao virus, although weakly, by cPCR when suspect tissues were inoculated and then incubated for prolonged periods on primary lake sturgeon cell lines but without evidence of CPE.…”
Section: Discussionsupporting
confidence: 73%
“…None of these possibilities can be ruled out from having occurred in the present study but, as we mentioned earlier, the presence of the virus in treated, municipal water seems unlikely, though not impossible. In fact, Drennan et al (2006) reported that the accidental introduction of as little as 100 ml of Kootenai River water resulted in fish testing positive for WSIV during the course of an experiment conducted in tanks receiving municipal water.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…During an outbreak, it is likely that ranavirus infects hosts via multiple routes of horizontal transmission. Although vertical transmission of iridoviruses has been shown in invertebrates [139], it has not been demonstrated for ranaviruses infecting vertebrates [140]. Attempts to test for vertical transmission have yielded mixed results [36,109].…”
Section: Ecologymentioning
confidence: 99%
“…The eggs were incubated and hatched in virus-free water and the resulting progeny were monitored for the presence of WSIV. Previous transmission studies showed that these fish were not infected with WSIV [18]. Histopathology examinations performed on these fish showed no evidence of lesions associated with WSIV infection and no disease outbreaks occurred during this study.…”
Section: Fish and Rearing Conditionsmentioning
confidence: 53%